Multimedia elements in the delivery of traditional prose of 'Asal Padi' among adolescents - Zakaria, Maslinda; Abu Bakar, Roslina; Seng, Tong Chong; Sujud, Arba’ie; Abd. Rahman, Ahmad Zufrie; Makmun, Rozaiman; Mohd Sarji, Kasmaizun Enuni (Human Resource Management Academic Research Society, 2021)
This study aims to look at the relationship of multimedia with folk literature. The objective of this study is to identify the multimedia features and their relationship with literary elements in the traditional prose of Asal Padi and to classify the multimedia features and literary features in the traditional prose of Asal Padi. Teenagers are now seen to be less interested in folk literature and even find it difficult to understand the content of the work. According to Nur Aisyah (2012), adolescents often describe literary material as a burden because the text and contexts are difficult to understand. Due to these factors, the study was conducted to identify multimedia features and their relationship with literary elements in the traditional prose of Asal Padi yet classify the multimedia features and literary elements in the traditional prose of Asal Padi. This study was conducted by using the 'KOMSAS’ courseware which contains the literary text of Asal Padi to be shown to early adolescents. This study incorporates Gagne (1975) Information Processing Theory. As a result, this study proved that combining multimedia elements and folk literature is the best method for adolescents to better understand traditional prose while producing a more positive appreciation effect.